A front tracking method for particle-resolved simulation of evaporation and combustion of a fuel droplet. (30th September 2018) - Irfan, Muhammad; Muradoglu, Metin
Highlights: A front-tracking method is developed for particle-resolved simulations of droplet evapo- ration. The CHEMKIN package is incorporated used to handle the chemical kinetics. A number of benchmark cases are studied to validate the numerical method. Combustion of a n-heptane droplet is simulated using a detailed chemistry model. Abstract: A front-tracking method is developed for the particle-resolved simulations of droplet evaporation and combustion in a liquid-gas multiphase system. One field formulation of the governing equations is solved in the whole computational domain by incorporating suitable jump conditions at the interface. Both phases are assumed to be incompressible but the divergence-free velocity condition is modified to account for the phase change at the interface. A temperature gradient based evaporation model is used. An operator-splitting approach is employed to advance temperature and species mass fractions in time. The CHEMKIN package is incorporated into the solver to handle the chemical kinetics. The multiphase flow solver and the evaporation model are first validated using the benchmark problems. The method is then applied to study combustion of a n-heptane droplet using a single-step chemistry model and a reduced chemical kinetics mechanism involving 25-species and 26-reactions. The results are found to be in good agreement with the experimental data and the previous numerical simulations for the time history of the normalized droplet size, the gasification rate, the peak temperature and the ignition delay times. The initial flame diameter and the profile of the flame standoff ratio are also found to be compatible with the results in the literature. The method is finally applied to simulate a burning droplet moving due to gravity at various ambient temperatures and interesting results are observed about the flame blow-off.